PERANCANGAN SISTEM INFORMASI MANAJEMEN PRAKTEK KERJA LAPANGAN BERBASIS WEB MENGGUNAKAN METODE AGILE - Falaah Abdussalaam; Andi Ramdani (POLITEKNIK PIKSI GANESHA, 2022)
This study aims to analyze and design of Internships Management Information System at PT Walden Global Services Bandung. Based on the research result, it turns out that the problems of internships data processing is still manual by using Microsoft Office applications and Google Spreadsheets, so that the participant's data information, quota amount which is still available and report processing became slower. To resolve these problems, it is necessary internships management information system design with an integrated database was needed for simplify the process of managing data, so that the information needed and report processing became faster, complete and precise. This information system is implemented using the PHP programming language with MySQL as its database. Agile was used as for the software development. The suggestions given is: 1) Organizing training on the procedures for the use of the new system; 2) Performing maintenance regularly so as not to damage; 3) Use recommended system specifications.